Revenge pornography on the internet - Evelyne Wanjiku (Communicare, 2022)
Revenge pornography, which is mainly understood as the publication of nude or intimate pictures of another person without their consent, is a phenomenon that is increasing in occurrence and constantly changing in the manner in which it is carried out. In Kenya, due to the absence of a proper regulatory mechanism, perpetrators continue to carry out their activities with resounding impact and devastating effects on the victims. This article uses discourse analysis to explore the motivations behind non-consensual pornography, reasons and motivations for its prevalence, which include revenge and punishment, entertainment/fun, the sexual objectification of women, “slut shaming”, and denigration of the victim’s character. The paper also looks at the legal and gendered aspects that allow the vice to continue being perpetrated. These include the lack of clearly defined laws that capture the various forms that revenge pornography can take and the lack of well-trained legal officers and law enforcers who can handle reported cases of revenge pornography. The article argues in favour of reform of the current legal framework in order to address non-consensual pornography as mediated by the tools of digital technology. This includes a clear legal definition of revenge pornography.